Mg-doped InSnO nanofiber field-effect transistor for methanol gas detection at room temperature. (14th May 2022) - Li, Linkang; Li, Jun; Fu, Wenhui; Jiang, Dongliang; Song, Yanjie; Yang, Qiuhong; Zhu, Wenqing; Zhang, Jianhua
Abstract: Research on high-performance gas sensors for detecting toxic and harmful methanol gas is still a very important issue. For gas sensors, it is very important to be able to achieve low concentration detection at room temperature. In this work, we used the electrospinning method to prepare Mg-doped InSnO nanofiber field-effect transistors (FETs) methanol gas sensor. When the Mg element doping concentration is 2.3 mol.%, InSnO nanofiber FET exhibits excellent electrical properties, including higher mobility of 3.17 cm 2 V −1 s −1, threshold voltage of 1.51 V, subthreshold swing of 0.42 V/decade, the excellent on/off current ratio is about 10 8 and the positive bias stress stability of the InSnO nanofiber FET through Mg doping has been greatly improved. In addition, the InSnMgO nanofiber FET gas sensor exhibits acceptable gas selectivity and sensitivity to methanol gas at room temperature. In the methanol gas sensor test at room temperature, when the methanol gas concentration is 60 ppm at room temperature, the response value of the InSnMgO nanofiber FET gas sensor is 81.92; and when the methanol concentration is 5 ppm, the response value is still 1.21. This work provides an effective and novel way to build a gas sensor at room temperature and use it to detect methanol gas at room temperature.